Contamination of Mercury (Hg) and Lead (Pb) in Seawater and Sediments in Coastal waters of Ohoitel Village, Southeast Maluku District - Nadira Fakoubun; Etty Riani; Majariana Krisanti (Postgraduate, University of Mataram, 2023)
Along with the increasing population in the coastal area of Ohoitel Village, it triggers the level of community settlement with an increase in anthropogenic activities. This study aims to determine the concentration of heavy metal mercury (Hg) and lead (Pb) dissolved in water and accumulated in sediments. Measurement of heavy metal levels using Atomic Absorption Spectrophometer (AAS). The results of the analyis og Hg content obtained in seawater at station I was 0.00100 ± 0.00007 mg/l, station II was 0.00096 ± 0.00026 mg/l and station III was 0.00101 ± 0.000026 mg/l. The results of Hg levels obtained in sediment at station I amounted to 0.08557 ± 0.0003 mg/l, station II amounted to 0.07761 ± 0.0004 mg/l and station III amounted to 0.08733 ± 0.0004 mg/l. The results of the analysis of Pb content in seawater at station I was 0.00050 ± 0.000003 mg/l, station II was 0.000047 ± 0.000003 mg/l and station III was 0.000038 ± 0.000005 mg/l. Based on the results obtained, it shows that it is still below the quality standard threshold that refers to PP RI No 22 0f 2021 for water and ANZECC 2000 for heavy metal Hg in sediment and USEPA for heavy metal Pb in sediment